2008
DOI: 10.5032/jae.2008.01028
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen-Year Enrollment Trends Related to the Three Components of Comprehensive Agricultural Education Programs

Abstract: The purpose of this study was to identify the agricultural education enrollment trends in Iowa using 15 years of data collected from 1991 to 2005. It was found that agricultural education enrollment, Supervised Agricultural Experience (SAE) participation, and FFA membership have grown. Using annualized growth rates, agricultural education enrollment (4.06%) grew more rapidly than SAE participation (1.65%) and FFA membership (2.39%). Although growth was realized in all three components, the widening gap between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…However, Retallick and Martin (2008) found that fewer agricultural education students participated in SAE and questioned why agriculture teachers fail to fully integrate the SAE portion into their agricultural education program.…”
Section: Introduction and Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…However, Retallick and Martin (2008) found that fewer agricultural education students participated in SAE and questioned why agriculture teachers fail to fully integrate the SAE portion into their agricultural education program.…”
Section: Introduction and Review Of Literaturementioning
confidence: 99%
“…Because of these findings and the related issues, many researchers have concluded that there is a perceived need to expand the concept and scope of SAE to meet the requirements of a more diverse clientele (Barrick et al, 1991;Graham & Birkenholz, 1999;Retallick & Martin, 2008;Roberts & Harlin, 2007;Steele, 1997;Wilson & Moore, 2007). Others have also identified a need for more in-service and dialogue related to the issues associated with SAE (Dyer & Osborne, 1995;Graham & Birkenholtz;Ramsey & Edwards, 2004;Wilson & Moore, 2007).…”
Section: Introduction and Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Throughout recent decades, SAE involvement within school-based agricultural education (SBAE) has declined nationwide (Dyer & Osborne, 1995;Retallick & Martin, 2008;Steele, 1997). In the early 1990's, over 85% of agricultural education students in Iowa conducted SAEs, by 2005, that number dropped to only 56% (Retallick & Martin, 2008). More recently, an average of 46% of students surveyed in Florida, Indiana, Missouri, and Utah reported conducting an SAE (Lewis, Rayfield, & Moore, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The need for greater engagement between teacher educators and school-based agriculture teachers on issues associated with SAEs has long been documented in agricultural education research (Dyer & Osborne, 1995;Graham & Birkenholz, 1999;Retallick & Martin, 2008;Wilson & Moore, 2007). Roberts and Dyer (2004) identified development of SAE opportunities for students was one of the highest professional development needs for school-based agriculture teachers.…”
Section: Literature Reviewmentioning
confidence: 99%